Exploring the Kairomone-Based Foraging Behaviour of Natural Enemies to Enhance Biological Control: A Review - Ayelo, Pascal M.; Pirk, Christian W. W.; Yusuf, Abdullahi A.; Chailleux, Anaïs; Mohamed, Samira A.; Deletre, Emilie (Frontiers in Ecology and Evolution, 2021)
Kairomones are chemical signals that mediate interspecific interactions beneficial to organisms that detect the cues. These attractants can be individual compounds or mixtures of herbivore-induced plant volatiles (HIPVs) or herbivore chemicals such as pheromones, i.e. chemicals mediating intraspecific communication between herbivores. Natural enemies eavesdrop on kairomones during their foraging behaviour, i.e. location of oviposition sites and feeding resources in nature. Kairomone mixtures are likely to elicit stronger olfactory responses in natural enemies than single kairomones. Kairomone-based lures are used to enhance biological control strategies via the attraction and retention of natural enemies to reduce insect pest populations and crop damage in an environmentally friendly way. In this review, we focus on ways for improving the efficiency of kairomone use in crop fields. First, we highlight kairomone sources in tri-trophic systems, and discuss how these attractants are used and detected by natural enemies searching for hosts or prey. Then we summarise some examples of field application of kairomones (pheromones versus HIPVs) in recruiting natural enemies. We highlight the need for future field studies to focus on the application of kairomone blends rather than single kairomones which currently dominate the literature on field attractants for natural enemies. We further discuss ways for improving kairomone use through attract and reward technique, olfactory associative learning, and optimisation of kairomone lure formulations. Finally, we discuss why the effectiveness of kairomone use for enhancing biological control strategies should move from demonstration of increase in the number of attracted natural enemies, to reducing pest populations and crop damage below economic threshold levels and increasing crop yield.